Perceptual effects of social salience: evidence from self-prioritization effects on perceptual matching. - Sui, J; He, X; Humphreys, G (2012)
We present novel evidence showing that new self-relevant visual associations can affect performance in simple shape recognition tasks. Participants associated labels for themselves, other people, or neutral terms with geometric shapes and then immediately judged whether subsequent label-shape pairings were matched. Across 4 experiments there was a reliable self-prioritization benefit on response times and perceptual sensitivity that remained across different presentation contexts (with self, best friend, and unfamiliar others in Experiment 1; with self, best friend, and neutral terms, and with self, mother, and neutral terms in Experiments 2A and 2B, respectively. Control studies in Experiment 3 indicated that the results did not reflect the length, concreteness, or familiarity of the words. The self-prioritization effect on shape matching also increased when stimuli were degraded (self shapes showing weaker effects of degradation) in Experiment 4A, consistent with self-information modulating perceptual processing. A similar effect was found when people associated different reward values to the shape in Experiment 4B. The results indicate that associating a stimulus to the self modulates its subsequent perceptual processing, and this may operate by self-associated shapes automatically evoking the reward system.